Analysis of Risk Factors for Acute Respiratory Infection in Terms of The Physical Environment in Jatimulya Village - Shihran, Laviany Putri; Sinaga, Evi Susanti (RRZ Scientific Publishing, 2023)
Acute respiratory infection (ARI) is currently a global primary health problem. WHO 2016 data shows that the incidence of ARI and the under-5 mortality rate are estimated at >40/1000 live births, or 15%-20% per year in the under-five group. ARI is an inflammatory reaction in the upper or lower respiratory tract. The risk of ARI occurring depends on three factors: the individual, behaviour, and environmental conditions. Environmental factors include lighting, humidity, area of ventilation or windows, types of walls, floors, roofs, and the distance from the house to the main road. Environmental factors, especially the house’s physical condition, are closely related to the magnitude of the community's risk of ARI. This study used a cross-sectional design. It was carried out in October 2022 and involved 148 mothers with toddlers in Jatimulya Village, Bekasi Regency. The instruments used were a rolling meter, a hygrometer, and a questionnaire with univariate and bivariate analysis. A chi-square test was used to determine whether there was a relationship. From the analysis results, it was found that the window width (p = 0.000) and humidity (p = 0.000) were related to the incidence of ARI, and the results were not related to the type of house wall (p = 0.069), the type of floor of the house (p = 0.196), and the distance between the house and the main road (p = 0.144) with the incidence of ARI. There is a significant relationship between window width and humidity and the incidence of ARI in toddlers, but there is no significant relationship between the type of wall, the type of floor, or the distance from the house to the main road.